Professional Xen virtualization. - Von Hagen, William, ....- (Indianapolis : Wiley, 2008)
With typical Wrox thoroughness, this book covers every aspect of virtualization on the Linux platform for administrators seeking to optimize the use of enterprise hardware, create virtual environments geared toward specific tasks, or establish a testing environment * Provides a complete foundation in virtualization, XEN, and competing approaches with in-depth discussions of installing, configuring, and using XEN, including detailed examples of XEN configuration files, system configuration files, and system-level configuration information * Offers details that help system administrator adopt XEN and justify its selection * Covers optimizing XEN, XEN hosts, and guest operating systems for maximum performance and reliability; using XEN in enterprise data centers; procedures and considerations for building custom guest operating systems to run as virtual machines on a XEN host; and much more